Encapsulation of Recombinant MOMP in Extended-Releasing PLGA 85:15 Nanoparticles Confer Protective Immunity Against a Chlamydia muridarum Genital Challenge and Re-Challenge - Sahu, Rajnish; Dixit, Saurabh; Verma, Richa; Duncan, Skyla A.; Smith, Lula; Giambartolomei, Guillermo H.; Singh, Shree R.; Dennis, Vida A. (Frontiers in Immunology, 2021)
Recently we reported the immune-potentiating capacity of a Chlamydia nanovaccine (PLGA-rMOMP) comprising rMOMP (recombinant major outer membrane protein) encapsulated in extended-releasing PLGA [poly (D, L-lactide-co-glycolide) (85:15)] nanoparticles. Here we hypothesized that PLGA-rMOMP would bolster immune-effector mechanisms to confer protective efficacy in mice against a Chlamydia muridarum genital challenge and re-challenge. Female BALB/c mice received three immunizations, either subcutaneously (SC) or intranasally (IN), before receiving an intravaginal challenge with C. muridarum on day 49 and a re-challenge on day 170. Both the SC and IN immunization routes protected mice against genital challenge with enhanced protection after a re-challenge, especially in the SC mice. The nanovaccine induced robust antigen-specific Th1 (IFN-, IL-2) and IL-17 cytokines plus CD4+ proliferating T-cells and memory (CD44high CD62Lhigh) and effector (CD44high CD62Llow) phenotypes in immunized mice. Parallel induction of antigen-specific systemic and mucosal Th1 (IgG2a, IgG2b), Th2 (IgG1), and IgA antibodies were also noted. Importantly, immunized mice produced highly functional Th1 avidity and serum antibodies that neutralized C. muridarum infectivity of McCoy fibroblasts in-vitro that correlated with their respective protection levels. The SC, rather than the IN immunization route, triggered higher cellular and humoral immune effectors that improved mice protection against genital C. muridarum. We report for the first time that the extended-releasing PLGA 85:15 encapsulated rMOMP nanovaccine confers protective immunity in mice against genital Chlamydia and advances the potential towards acquiring a nano-based Chlamydia vaccine.